KOMUNIKASI DAN KONFLIK: KERAGAMAN ANTAR ETNIS DI DESA DEHES - Memoriance, Memo (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2024)
Dehes Village has a lot of diversity in both customs and religion. This diversity can be a double-edged knife that can occur collaboration and conflict between ethnicities. This research aims to describe the conflicts that occur in Dehes village and how the importance of communication in maintaining diversity in Dehes village. This research is designed as a descriptive qualitative research. Data were collected through observation, interviews, documentation. Data analysis uses data reduction, data verification. The results revealed that the function of communication in maintaining inter-ethnic diversity is Communication, especially for village heads and religious leaders, is also an intermediary in conveying expectations about conflicts that arise when providing counselling to residents/ethnic groups living in a religious environment. The role of communication in resolving conflicts is to hold deliberations for consensus to gather tribal leaders and religious leaders for deliberation. In addition, to prevent the conflict from reoccurring is to hold a lecture or dharma discourse with material on ethnic and religious diversity using their respective holy books.